Islamic leadership in the European lands of the former Ottoman and Russian Empires: legacy, challenges and change - Račius, Egdūnas; Željazkova, Antonina (Muslim minorities, 2018)
Rationale of the book / Antonina Zhelyazkova and Egdūnas Račius -- Historical retrospective on muftiship: muftis, state muftis and official muftis / Jakob Skovgaard-Petersen -- Ottoman and Yugoslav legacy / Dino Mujadzevic -- Albania / Olsi Jazexhi -- Bosnia and Hercegovina / Aid Smajic -- Bulgaria / Aziz Shakir -- Croatia / Dino Mujadzevic -- Kosovo / Armend Mehmeti and Memli Sh. Krasniqi -- Romania / Irina Vainovski-Mihai -- Serbia / Srdan Barisic -- Slovenia / Marko Hajdinjak -- Islamic leadership: the Russian and Soviet legacy / Galina M. Yemelianova -- Belarus / Dasa Slabcanka --Lithuania / Egdūnas Račius -- Poland / Agata S. Nalborczyk --Ukraine / Mykhaylo Yakubovych, Vitalii Shchepanskyi and Ayder Bulatov -- Epilogue: Drawing parallels / Egdūnas Račius and Antonina Zhelyazkova